Sistem Pendukung Keputusan Penentuan Produk Otomasi Paling Diminati Dengan Metode Multi Factor Evaluation Process - Laila Ersa; Ibnu Satria Fajar Al Afif; Syarif Hidayatulloh (Paradigma - Jurnal Komputer dan Informatika, 2022)
Products are goods or services that are traded to fulfill needs. Many products sold at PT Autonics Indonesia make it difficult for the company to determine which products are most interested. The current product supply system still uses a manual system with Microsoft Excel and there is no decision support system for determining the most interested product with the proper method so that the decisions taken are less accurate, effective and efficient. The method proposed in this research is Multi Factor Evaluation Process (MFEP) method with the purpose to apply a decision support system to assist the company in determining the most interested products, make the decision easier, more accurate, effective. In this research, 5 (five) factors were used to determine the most interested products, that is: price, type, quality, inventory and warranty. The results acquired in this research are ranking of the most interested automation products sorted from the highest to lowest from Total Evaluation Weight (TEW) value. Based on the calculations performed by Multi Factor Evaluation Process (MFEP) method, 5 (five) alternatives were obtained with the highest Total Evaluation Weight (TEW) value, including: Fiber Optic Sensors with a value of 4.90, Control Switch with a value of 4.75, Digital Panel Meters with a value of 4.60, Temperature Controllers with a value of 4.35 and Timers with a value of 4.30 which will be a solution to simplify the determination of the most interested products at PT Autonics Indonesia.